People, power and politics: Developing a public sector sharing economy. Issue 126 (November 2021) - Cheetham, Fiona; Lever, John B.
Highlights: Key distinctions between 'collaboration' and 'reciprocity' styles of sharing. Public sector sharing comprises hybridized forms of sharing. Public sector sharing is more complex than other forms of sharing. Heterogeneity in governance strategies is required in public sector sharing. Abstract: In this paper, we explore how a local authority in the North of England attempted to develop a public sector sharing economy to deliver welfare services in new and innovative ways. The study examines how and why public sector sharing differs from commercial and not-for-profit sharing, and assesses the implications of this for getting public sector sharing economies off the ground. Our analysis suggests that public sector sharing comprises hybridized forms of sharing, in which some aspects align with a 'collaboration' style of sharing economy, not too dissimilar to typical marketplace exchange relationships. In other aspects, however, public sector sharing resembles a 'reciprocity' style of sharing more usually associated with the 'sharing culture' in evidence in not-for-profit sharing economies. In the public sector sharing economy under investigation, characteristics of state 'redistribution' also linger, as the local authority seeks to move away from traditional economic arrangements towards the sharing economy. Overall, our study shows that public sector sharing appears to exhibit a much higher degree of complexity than other types of sharing economy, which arises from the different motivations, values and ways of working among the various organizations and community groups involved. We conclude that an imperative of heterogeneity in governance strategies is needed to match the heterogeneity in evidence in the public sector sharing economy being developed.